Noise in neonatal intensive care units: a short review - Alberto Alves Carvalhais, Carlos (2019)
Prematurity and low birth weight of newborns lead to the need of a special care in neonatal units, and their permanence in these places can be extended for a long period. Indoor environmental conditions, such noise levels above the recommended, may induce some risks, not only for the newborns development, but also for health care staff. This literature review aims to examine the studies related to noise in neonatal intensive care units to understand the sources and effects of noise, as well as some strategies to reduce noise exposure. The search strategy included an electronic search in databases (ISI Web of Knowledge and PubMed) of scientific articles published in English/Portuguese between 2000-2017. Studies providing data on noise levels found in the neonatal units, the effects on health of newborns and staff and the measures to minimize these effects were included. The exclusion criteria were as follows: duplicate printings; nonEnglish/Portuguese language; editorials, letters, patents, errata, meeting abstracts and conference papers. PRISMA methodology was followed to perform the review. Twenty-two articles were considered for full analysis. It is important to note that some potentially relevant studies were rejected due to language criteria. It was found that the noise levels to which the newborns and staff are exposed in NICU, often exceeds the recommended levels for these spaces. Evidence also shows several adverse health effects for newborns and health care staff perceptions of noise. There is no consensus regarding the best intervention to reduce noise levels.